Nano-structured strategies in combatting neurodegeneration - Prasanth, Mani Iyer; Mallya, Anjali R.; Cho, William C.; Mundekkad, Deepa (Frontiers in Bioengineering and Biotechnology, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that is characterized by the loss of dopaminergic neurons, leading to severe motor and cognitive impairments. Recent advancements in nanomedicine and nano-structured technologies have opened new avenues for targeted drug delivery and neuroprotection, improving therapeutic efficacy and diagnostic accuracy. By harnessing innovative nanotechnological platforms, researchers aim to enhance clinical trial outcomes and refine early-stage diagnostic advancements, offering hope for improved disease management. However, since the pathophysiology of PD is diverse, there are limited treatment options available. This review explores the potential of the recent nanostructured technologies in managing the complexities of PD. Deliberations on the insights from nanomedicine, neurobiology, and material science, on how these emerging and technologically sound nanostructured approaches help in the prevention, diagnosis and treatment of PD will be discussed. Further, the role of nanocarriers in targeted drug delivery involving nanoscale materials specifically for neuroprotection and regeneration will be discussed with special emphasis on the role of nanotechnology in advancing diagnostic methodologies. Additionally, we aim to chart a course for future research directions, with special reference to innovative approaches in disease diagnosis. The various therapeutic approaches, along with the ongoing clinical trials and real-world applications, are expected to add value to the efforts of the researchers worldwide to enhance therapeutic efficacy and patient outcomes in PD.